ANALISIS MOTIVASI KERJA PERAWAT DIRUMAH SAKIT EKA HOSPITAL PEKANBARU - Nita Elpiya; La Ode Syarfan (VALUTA, 2018)
The purpose of this research is to know about nurse work motivation and to know policy of hospital in improving work motivation of nurse. This research was conducted at Hospital Eka Hospital Pekanbaru. Types and data sources used are primary and secondary data, data collection techniques are obtained through questioners, interviews and observation. The number of samples taken from population nurse 270 people as many as 54 people. The sampling technique used by the researcher is using simple random sampling. Data analysis used is descriptive analysis. The results of the whole study showed that the opinion of the respondents about the motivation of nurses at Hospital Eka Hospital Pekanbaru is in the category strongly agree.